Jan Švankmajer’s Kunstkammer: Every thing means everything - Brzezińska, Anna Maria (Journal of Education Culture and Society, 2020)
Thesis. Jan Švankmajer’s Kunstkammer is a project with a complex constellation of meaning that defies clear-cut categorization in the context of Pomian’s theory of semiophores. Discussed concepts. The paper describes the kunstkammer art project created by Jan Švankmajer, a Czech surrealist, in the context of Pomian’s theory of semiophores and compares it to traditional and historical equivalents, using the concepts of micro- and macrocosm, the world as a stage (Theatrum Mundi), hermeticism, and alchemy. Results and conclusion. Jana Švankmajer’s Kunstkammer should be analyzed primarily in the individual and subjective context, rather than in the social one.  Originality/cognitive value of the approach. Pomian has described many examples of traditional kunstkammers, but there are also several modern collections that have not yet been described in the literature.